Plan de negocio para la implantación de una ferretería en el sur de Quito - Fernández Coronel, David Reinaldo (2012)
The business plan focuses on the implementation of a hardware store located in the south of Quito, specifically Quitumbe this because it is a highly residential, and hardware can develop their capabilities to provide products and services. The business focus is to provide differentiated services and we locate in the consumers mind as pioneers in offering not just products but a full combo, through personnel assisting in installation, repair and maintenance. The business idea comes from research and the positive results that people accept the idea of finding services with the same facility that there is any product for a hardware store. One of the most important strength is that it clearly has previously trained staff and appropriate care for both client and service offerings, this is the basis to reflect consumer confidence, taking into account that people in their first purchases we are assessing and this will be vital for future purchases and recommendations. Shuttle will be provided in the case of materials such as iron and cement as easily discard any product in the event that the customer needs, for which there will be a truck in case of large materials, and two trucks for deliveries of lower volume. For proper planning of the hardware market income fell developing a financial analysis which showed positive results from several aspects, showing that there is a real and tangible opportunity for business growth and good performance in future years. The Net Current Value generated by the conservative stage is of USD 2.219.13 demonstrating thus to surpass the initial investment and to generate a positive excess for the company, of the same way was generated an Internal Return Rate of 31% in the same stage, to confirm the viability of the same. The company will be formed with an initial investment of USD 88516. Will generate projected minimal profitability of USD 8,132.32 in the first year, USD 22,727.67 in the second year, USD 39,819.23 in the third year, USD 70048.23 in the fourth year and finally USD 105,539.02 in the fifth year.